Interleukin-35 Suppresses Interleukin-9-Secreting CD4+ T Cell Activity in Patients With Hepatitis B-Related Hepatocellular Carcinoma - Zhang, Qian; Yang, Lanlan; Liu, Siqi; Zhang, Mengyao; Jin, Zhenjing (Frontiers in Immunology, 2021)
Chronic hepatitis B virus (HBV) infection induces dysfunction of immune response and chronic liver damage. However, the mechanisms that account for HBV-related hepatocellular carcinoma (HCC) are poorly understood. The aim of present study was to investigate the modulatory role of interleukin (IL)-35, an immunosuppressive cytokine, to IL-9-secreting T cells in hepatitis B-related HCC. Twenty-two HBV-related HCC patients, twenty-seven chronic hepatitis B (CHB) patients, and eleven controls were enrolled. Serum IL-35 and IL-9 concentration was measured by ELISA. Peripheral and liver-infiltrating non-specific and HBV-specific Th9 and Tc9 cells were assessed by flow cytometry. The regulatory activity of IL-35 to peripheral and liver-infiltrating Th9 cells was assessed in co-culture system between CD8+ T cells and HepG2.2.15 cells. Serum IL-35 was up-regulated, while IL-9 was down-regulated in HBV-related HCC patients compared with in CHB patients and controls. Peripheral non-specific and HBV-specific Th9 cells, but not Tc9 cells, were decreased in HBV-related HCC patients. Liver-infiltrating non-specific and HBV-specific Th9 cells were also reduced in HCC tumor sites. CD8+ T cells from CHB and HBV-related HCC patients revealed decreased cytotoxicity compared with those from controls. Autologous Th9 cells mediated the elevation of CD8+ T cell cytotoxicity, and this process was depending on IL-9 secretion. Recombinant IL-35 stimulation inhibited IL-9 secretion and PU.1 mRNA expression in non-specific and HBV-specific Th9 cells, leading to the suppression of Th9-mediated CD8+ T cell cytotoxicity in CHB and HBV-related HCC patients. Our current data indicated that IL-35 might dampen non-specific and HBV-specific Th9 cells activity in HBV-related HCC patients.